2023
DOI: 10.1111/nph.18968
|View full text |Cite
|
Sign up to set email alerts
|

CBL1/9–CIPK23–NRAMP1 axis regulates manganese toxicity

Abstract: Summary Manganese (Mn) is an essential micronutrient in plants. However, excessive Mn absorption in acidic soils can cause Mn toxicity, which adversely affects plant growth and crop yields. At present, acidic soils cover c. 30% of the Earth's surface. However, the mechanism underpinning Mn uptake remains largely unknown. We identified cbl1/9 and cipk23 mutants exhibiting high‐Mn‐sensitive phenotype through the reverse genetics method. Furthermore, we identified the CIPK23 phosphorylated NRAMP1 through a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Striking is the fact that CIPK23 seems to regulate the two major Mn transporters at the plasma membrane NRAMP1 and IRT1 ([10,28] and the present work). This attests to the central role of this kinase in the control of Mn entry within the cell.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Striking is the fact that CIPK23 seems to regulate the two major Mn transporters at the plasma membrane NRAMP1 and IRT1 ([10,28] and the present work). This attests to the central role of this kinase in the control of Mn entry within the cell.…”
Section: Discussionmentioning
confidence: 60%
“…This attests to the central role of this kinase in the control of Mn entry within the cell. We and others [10,28] have shown that cipk23 and cbl1 cbl9 are sensitive to Mn excess confirming their incapacity to control Mn entry in the plant. Given that NRAMP1 and IRT1 contribute to Mn acquisition probably with different affinities, it would be interesting to further investigate the contribution of each of these transporters in the Mn hypersensitive phenotype of the mutants and more generally in the cellular response to Mn excess.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…AtNRAMP3 and AtNRAMP4 are located on the vacuole membrane and are responsible for releasing Mn or Fe from the vacuole (Lanquar et al 2005(Lanquar et al , 2010. AtNRAMP6, located on the PM, plays an important role in the detoxification of cadmium (Cd) (Cailliatte et al 2009;Zhang et al 2023b). In rice, OsNRAMP5 is located at the far end of the outer and endodermis cells, and is the main transporter of Mn and Cd, responsible for transporting Mn and Cd from the external solution to the root cells (Sasaki et al 2012;Ueno et al 2015).…”
Section: Introductionmentioning
confidence: 99%